Mucosal Mast Cells Response in the Jejunum of Ascaridia galli-Infected Laying Hens - Darmawi; U. Balqis; M. Hambal; R. Tiuria; Frengki; B. P. Priosoeryanto (Media Peternakan, 2013)
Intestinal defense mechanism against helminthes parasitic nematode to be associated with mucosal mast cells reaction. The aim of this research was to examine the effect of infection by Ascaridia galli parasite to trigger mucosal defense based on mucosal mast cells response in laying hens. Amount of ten head laying hens 12-wk old were divided into two groups containing five chickens of each. The first group, chickens were left as un-infected controls. The second group, chickens were infected orally with 1,000 embryonated eggs of A. galli. Mucosal mast cell responses were assayed by in situ jejunal mast cell counts in stained serial histological sections with Alcian blue (pH 0.3) and Safranin-O (pH 0.1) of the jejunum. Mucosal mast cells response were observed and counted on days 14 post infection. The result showed that A. galli infection was able to increase significantly (P<0.05) mast cells response. This research concluded that the A. galli infection can trigger the involment of mucosal mast cells response in jejunal defense of laying hens against parasitic diseases caused by A. galli.